Enhancing the Efficiency of a Dye-Sensitized Solar Cell Based on a Metal Oxide Nanocomposite Gel Polymer Electrolyte - Saidi, Norshahirah Mohamad; Omar, Fatin Saiha; Numan, Arshid; Apperley, David C.; Algaradah, Mohammed M.; Ramesh, Kasi; Avestro, Alyssa-Jennifer; Ramesh, Subramaniam (American Chemical Society, 2019)
To overcome the critical limitations of liquid-electrolyte-based dye-sensitized solar cells, quasi-solid-state electrolytes have been explored as a means of addressing long-term device stability, albeit with comparatively low ionic conductivities and device performances. Although metal oxide additives have been shown to augment ionic conductivity, their propensity to aggregate into large crystalline particles upon high-heat annealing hinders their full potential in quasi-solid-state electrolytes. In this work, sonochemical processing has been successfully applied to generate fine Co3O4 nanoparticles that are highly dispersible in a PAN:P(VP-co-VAc) polymer-blended gel electrolyte, even after calcination. An optimized nanocomposite gel polymer electrolyte containing 3 wt % sonicated Co3O4 nanoparticles (PVVA-3) delivers the highest ionic conductivity (4.62 × 10-3 S cm-1) of the series. This property is accompanied by a 51% enhancement in the apparent diffusion coefficient of triiodide versus both unmodified and unsonicated electrolyte samples. The dye-sensitized solar cell based on PVVA-3 displays a power conversion efficiency of 6.46% under AM1.5 G, 100 mW cm-2. By identifying the optimal loading of sonochemically processed nanoparticles, we are able to generate a homogenous extended particle network that effectively mobilizes redox-active species through a highly amorphous host matrix. This effect is manifested in a selective 51% enhancement in photocurrent density (JSC = 16.2 mA cm-2) and a lowered barrier to N719 dye regeneration (RCT = 193 ω) versus an unmodified solar cell. To the best of our knowledge, this work represents the highest known efficiency to date for dye-sensitized solar cells based on a sonicated Co3O4-modified gel polymer electrolyte. Sonochemical processing, when applied in this manner, has the potential to make meaningful contributions toward the ongoing mission to achieve the widespread exploitation of stable and low-cost dye-sensitized solar cells. Copyright © 2019 American Chemical Society.